A Criminal and Legal Assessment of Collaborationism: A Change of Views in Connection with Russia’s Military Aggression against Ukraine - Natalia Antonyuk (Access to Justice in Eastern Europe, 2022)
The dynamics of amendments to the Criminal Code of Ukraine after the start of the war show that the criminal law was not sufficiently ready for application during the war. First of all, a number of acts that are socially dangerous have not been singled out as criminal acts. Some existing articles needed to be amended to differentiate criminal liability. This article is based on the use of comparative, historical, and statistical methods, which are the basis for proving the grounds for criminalisation or differentiation of acts, taking into account the martial law caused by the war waged by the Russian Federation against Ukraine. Following the research conducted, we consider it possible to state that collaboration activities have a high level of public danger and should therefore be criminalised. The severity of punishment for such actions depends on the type of collaborationism. Scholars and law enforcers in countries analysing Ukraine’s experience and changes in criminal law in connection with the war should clearly delineate the criminal range of acts of treason and analyse whether there are any socially dangerous acts